COPYRIGHT PROTECTION ON WORKS GENERATED BY ARTIFICIAL INTELLIGENCE - Aronov, Ansagan Kuspanovich; Idrysheva, Sara Kimadievna (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
Nowadays people’s lives are hugely affected by artificial intelligence (AI). For example, machines text quickly, develop software, and create different types of arts. One may notice that many of the sport and business news which are accessible on the net are written by machines. According to the current legal framework of many states, AI-generated works are generally viewed as a simple tool. However, with the development of advanced AI machines, this perspective has undergone a significant shift. The emergence of AI has hugely posed challenges to intellectual property law, in particular copyright. In copyright sphere, AI-generated machines have risen some legal disputes whether AI can be the author of creative works, how AI works need to be protected or who owns the rights for such works. The paper aims to address the aforementioned questions and to clarify copyright issues arising from AI machines. The purpose of this paper is to identify the characteristics of legal regulations governing copyrighted works produced by AI machines in developed countries and subsequently offer relevant recommendations to improve national (Kazakh) copyright law concerning AI-generated machines. Based on foreign practice, the author argues that when it comes to creative works generated by computer machines, the individual who has made the necessary arrangements for the creation of such works should be considered the author.